Fenomena Pembentukan Variasi Sosiolek dalam Interaksi Sosial Masyarakat Berdasarkan Latar Belakang Sosial Penutur - Lingga Wulandari; Rina Andriani; Desma Yuliadi Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Language in urban life constantly experiences variations along with the diversity of social backgrounds of its speakers. Cilegon as an industrial city with a high level of social heterogeneity is one area that represents this phenomenon, especially in the Perumnas Cibeber area (Cluster Gagak), Cibeber District. This study aims to describe the phenomenon of the formation of sociolect variations based on the social backgrounds of speakers in urban society in Cilegon. This study uses a qualitative approach with a phenomenological research type because it is directed to understand in depth how sociolect variations are experienced and interpreted by speakers in natural contexts. Data sources consisted of eight urban community informants with diverse backgrounds of age, education, occupation, and regional origin. Data were collected through in-depth interviews, non-participatory observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the formation of sociolect variations is influenced by four main social backgrounds, namely age and social environment, occupation and professional environment, education and academic environment, and regional origin and family environment. These four factors do not operate in isolation, but rather are interconnected, allowing a speaker to use different forms of language depending on the social environment and the interlocutors they encounter. This finding confirms that sociolect variation in urban communities is dynamic and contextual, a direct reflection of the social heterogeneity of its speakers.